A rare case of successful pain control in a prostate cancer patient with bone metastasis undergoing hemodialysis by measuring the serum oxycodone level and using an activity tracker - Yoshihisa Mimura; Yosuke Sugiyama; Taku Naiki; Tomoya Kataoka; Yoshihiko Tasaki; Toshiki Etani; Nami Tomiyama; Nayuka Matsuyama; Kunihiro Odagiri; Kazunori Kimura; Takahiro Yasui (Current Problems in Cancer: Case Reports, 2022)
Background: The number of patients with cancer and end-stage renal disease is increasing because of the success of hemodialysis treatment. However, methods for monitoring opioids to control severe pain induced by cancer remain unsatisfactory. Case Presentation: A 72-year-old male, with a history of hemodialysis induced by diabetic nephropathy for 16 years and prostate cancer for three years, was diagnosed with metastasis in his 12th thoracic and 2nd lumbar vertebrae, and treated with analgesic pain management (oxycodone, acetaminophen, and pregabalin) and radiotherapy. Case management and outcome: Concern about poor pain control induced by the instability of blood opioid levels caused by hemodialysis meant the serum concentration of oxycodone was measured pre- and post-dialysis. Since the impact of pain on daily life cannot be fully assessed by pain score questionnaires, we also monitored patient activity using a wrist band-type activity tracker. A pain numeric rating score was used. Inter-day variations in the number of steps per day were observed. The relationship between pain score and blood concentrations of oxycodone pre- and post-dialysis was analyzed. The serum concentration of oxycodone was stable, even after hemodialysis, and the patient's pain gradually decreased. Conclusion: By monitoring the serum concentration of oxycodone, we obtained good pain control for bone metastasis in a patient with prostate cancer undergoing dialysis. We also monitored physical activity using an activity tracker. These findings might be useful in the selection of analgesics during the control of cancer pain in dialysis patients and allow for the objective management of opioid dosage.